The complete guide to RTI : an implementation toolkit - Burton, Dolores; Kappenberg, John (Corwin, 2012)
Provides an overview of RTI (response to intervention) to professional educators in K-12 schools and to teacher candidates in colleges and universities, demonstrating innovative ways to use RTI to inform instruction and guide curriculum development in inclusive classroom settings. Includes strategies, techniques, and checklists for evaluating existing programs and implementing RTI effectively.